The Role of Indigenous Communities in Protecting The Environment After The Entry of Companies - Hattu, Vondaal Vidya; Tahamata, Lucia Charlota Octovina (Faculty of Law, Universitas Pattimura, 2024)
Introduction: The many cases of land disputes involving indigenous communities have created a bad image for this community.Purposes of the Research: The rights of indigenous peoples as well as the legal substance that forms the basis for the implementation of development in safeguarding the environment after the entry of the CompanyMethods of the Research: The method used is normative juridical with qualitative analysis.Results of the Research: The noble values in the lives of indigenous peoples seem to have disappeared due to a number of